Pulse-Propagation Modeling and Experiment for Femtosecond-Laser Writing of Waveguide in Nd:YAG - Tao Feng (Crystals, 2019)
In this work, unidirectional pulse propagation equation (UPPE) modeling is performed to study the nonlinear laser-mater interaction in silicon and Nd:Y3Al5O12 (Nd:YAG) crystals. The simulation results are validated with reported experimental results for silicon and applied to Nd:YAG crystals with experimental validation. Stress-induced waveguides are written in Nd:YAG crystals using 515 nm, 300 fs pulses at a 1 kHz repetition rate. Waveguides having a mean propagation loss of 0.21 ± 0.06 dB/cm are obtained, which is lower than the previous reported values for Type-II waveguides written in Nd:YAG crystals. The modeling and experimental results consistently show that the modification (waveguide track) depth increases with input energy. A detailed analysis is presented to control the modal properties of the waveguide in the context of UPPE simulation.